Synthesis and electrical properties of La0.8Ca0.2Ti0.8Sc0.2O3−δ perovskite for energy applications. Issue 2 (21st July 2020) - Bradha, M; Kavitha, K; Vijayaraghavan, T; Yuvaraj, S; Ashok, A M
Abstract : La0.8 Ca0.2 Ti0.8 Sc0.2 O3− δ (LCTSO) complex perovskite was synthesized through the sol–gel synthesis method. The structural and electrical properties of LCTSO were investigated in this study. X-ray diffraction analysis revealed single-phase orthorhombic crystal structure formation along with a slight change in the unit cell volume after doping with calcium (Ca) and scandium (Sc). The morphology of the sintered pellet of LCTSO was studied through scanning electron microscopy and transmission electron microscopy techniques. The alternating-current impedance spectroscopy technique was used to study the total conductivity of the materials from 300 to 800°C in air atmosphere. The substitution of calcium (Ca 2+ ) and scandium (Sc 3+ ) ions in the higher-valent cationic sites resulted in the creation of oxygen vacancies in the lattice. The created oxygen vacancies provided an energy barrier for charge diffusion, which led to an increase in the conductivity of LCTSO, with a maximum value of 2.71 × 10 −3 S/cm at 750°C. The synthesized materials exhibit enhanced mixed conductivity compared with the undoped LaTiO3− δ and can be suitable for many energy generation applications, particularly for solid oxide fuel cells.